1994
DOI: 10.1002/bjs.1800811140
|View full text |Cite
|
Sign up to set email alerts
|

Experimental colonic healing in relation to timing of 5-fluorouracil therapy

Abstract: In an experimental study resembling clinical use of adjuvant 5-fluorouracil (5-FU) treatment of colorectal carcinoma, 97 male Wistar rats were operated on with a standardized left colonic resection. Treatment was given as a daily intraperitoneal injection. The animals were randomized to one of four groups: early treatment with 5-FU 20 mg/kg or saline 0.1 mol/l from the day of operation to day 7 after operation, and delayed treatment with 5-FU 20 mg/kg or saline 0.1 mol/l from the third day after operation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
36
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 18 publications
10
36
0
5
Order By: Relevance
“…Weiber et al investigated the relation between the timing of 5-fluorouracil treatment introduction and anastomosis status. Their results showed that delayed treatment resulted in an uncomplicated healing process, whereas beginning the regime on the day of surgery was connected with detrimental effects on anastomosis status [42]. Similar observations were obtained in the studies by Kanellos et al who compared early and delayed combined treatment with 5-fluorouracil and interferon or folinic acid [43,44].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Weiber et al investigated the relation between the timing of 5-fluorouracil treatment introduction and anastomosis status. Their results showed that delayed treatment resulted in an uncomplicated healing process, whereas beginning the regime on the day of surgery was connected with detrimental effects on anastomosis status [42]. Similar observations were obtained in the studies by Kanellos et al who compared early and delayed combined treatment with 5-fluorouracil and interferon or folinic acid [43,44].…”
Section: Discussionsupporting
confidence: 61%
“…and Kanellos et al, delayed therapy cycles begun on the third and fourth days after surgery, respectively, were connected with significantly less detrimental influence on the healing process. Early treatment was introduced on the day of surgery in those studies and resulted in visible impairment of the anastomosis status [42,44]. In our study, treatment began on the second post-operative day.…”
Section: Discussionmentioning
confidence: 81%
“…These drugs are usually administered intravenously, although several studies have proved that, after intraperitoneal injection, high concentrations of 5-fluorouracil are achieved locally, e.g. in the liver [1][2][3]. It is already known that the early intraperitoneal administration of adjuvant chemotherapy destroys the cancer cells which have been disseminated during operation, and inhibits the micrometastases which can lead later to local failure, intraperitoneal dissemination, regional recurrence and hepatic metastases [1,2,[4][5][6][7][8].…”
mentioning
confidence: 99%
“…Immediate i.p. 5‐FU also causes anastomotic leakage 31. Continuous 5‐FU infusions enabled the use of greater daily dosages and appeared safer than injecting a bolus of 5‐FU 32.…”
Section: Discussionmentioning
confidence: 99%